Human Capital Formation, Life Expectancy, and the Process of Development - Cervellati, Matteo; Sunde, Uwe (American Economic Review, 2005)
We provide a unified theory of the transition in income, life expectancy, education, and population size from a nondeveloped environment to sustained growth. Individuals optimally trade off the time cost of education with its lifetime returns. Initially, low longevity implies a prohibitive cost for human capital formation for most individuals. A positive feedback loop between human capital and increasing longevity, triggered by endogenous skill-biased technological progress, eventually provides sufficient returns for widespread education. The transition is not based on scale effects and induces population growth despite unchanged fertility. A simulation illustrates that the dynamics fit historical data patterns.